Human Capital and Regional Development in Europe A Long-Run Comparative View - Diebolt, Claude; Hippe, Ralph (Cham : Springer International Publishing : Imprint: Springer, 2022)
Human capital is of utmost importance for the future of our knowledge economies and societies. However, it is unequally distributed in Europe, contributing to marked spatial patterns of economic prosperity within and across countries. In many cases, these patterns have a long history. To understand them better, it requires to go back in time, when mass schooling was starting to become a reality across Europe. Taking a long-run perspective over more than 150 years, this book shows the development and the distribution of human capital in the regions of Europe and its connections with the economy. It provides insights into recent research findings in this area, including theoretical advances and the use of new empirical data.
Chapter 1. Introduction -- Chapter 2. Regional human capital inequality in Europe -- Chapter 3. Spatial clustering of numeracy and literacy -- Chapter 4. Human capital and market access in the European regions -- Chapter 5. The long-run impact of human capital on innovation and economic growth in the regions of Europe -- Chapter 6. Lessons from human capital evolution over the last 200 years -- Chapter 7. Conclusion and future directions for research.
Keywords: Economic history; Regional economics; Spatial economics; Economic geography; Econometrics; Economic development; Economic History; Regional and Spatial Economics; Economic Geography; Quantitative Economics; Economic Development, Innovation and Growth